(untitled) (Historia, 2021)
In a multilingual society with a complex history of identity politics, language medium in South African higher education is a topic that frequently recurs and remains emotionally charged. As single medium institutions dominated the higher education landscape in the previous century, the history of multilingual educational endeavours has been somewhat neglected. This article considers the way the roles of different languages were negotiated at the Transvaal University College, forerunner of the University of Pretoria. It will examine not only the official life of the institution, but consider the way languages were dealt with in the college’s student life. Motivations behind the introduction of Afrikaans as a second medium of instruction will also be considered. The way these events and circumstances related to notions of broad South Africanism, on the one hand, and growing Afrikaner nationalism on the other, will be highlighted. Some of the complexities which related to the bilingual policy of the college, as well as the defence of the policy by college authorities will be examined. In this way, the pitfalls and motivations behind the relatively short period of official bilingualism at the college will be investigated.